2016
DOI: 10.1038/srep33949
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gefitinib off-targets using a structure-based systems biology approach; their validation with reverse docking and retrospective data mining

Abstract: Gefitinib, an EGFR tyrosine kinase inhibitor, is used as FDA approved drug in breast cancer and non-small cell lung cancer treatment. However, this drug has certain side effects and complications for which the underlying molecular mechanisms are not well understood. By systems biology based in silico analysis, we identified off-targets of gefitinib that might explain side effects of this drugs. The crystal structure of EGFR-gefitinib complex was used for binding pocket similarity searches on a druggable proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 30 publications
(32 reference statements)
1
30
0
Order By: Relevance
“…To demonstrate the power of BioGPS, in Fig 1F we focus on two allosteric cavities that we found in the Epidermal Growth Factor Receptor (EGFR) and the Mitogen-Activated Protein Kinase 2 (MAPK2). While distant in the kinase phylogeny, off-target interactions between EGFR and MAPK2 have been previously detected in high-throughput kinase inhibition screens [24, 25]. The allosteric pockets that we found, when superimposed, show similar shape and non-bonded hydrophobic and polar patterns (S1F Fig), hinting towards a structural hypothesis for the MAPK2-EGFR cross-pharmacology.…”
Section: Resultssupporting
confidence: 68%
“…To demonstrate the power of BioGPS, in Fig 1F we focus on two allosteric cavities that we found in the Epidermal Growth Factor Receptor (EGFR) and the Mitogen-Activated Protein Kinase 2 (MAPK2). While distant in the kinase phylogeny, off-target interactions between EGFR and MAPK2 have been previously detected in high-throughput kinase inhibition screens [24, 25]. The allosteric pockets that we found, when superimposed, show similar shape and non-bonded hydrophobic and polar patterns (S1F Fig), hinting towards a structural hypothesis for the MAPK2-EGFR cross-pharmacology.…”
Section: Resultssupporting
confidence: 68%
“…Unlike EGFR antibodies, iEGFRs have not shown clinical efficacy in colorectal cancer; however, they are used clinically to successfully treat other cancers (13). As with most small molecules, iEGFRs have numerous effects within cells that are separate from their intended target (19)(20)(21). Although these effects may technically be referred to as "offtarget" effects, the contribution of these EGFR-independent effects may be an important mechanism contributing to the anticancer properties of these small molecules.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate how menin inhibition synergizes with iEGFRs to repress colorectal cancer cells in an EGFR-independent manner, we sought to examine whether iEGFR-induced ER stress is involved (19)(20)(21)(22). Gefitinib alone was found to induce ER stress in HT-29 cells as it increases CHOP expression and XBP1 splicing (Fig.…”
Section: Menin Inhibition Synergizes With Gefitinib and Thapsigarginmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the signals promoting OPC differentiation into myelinating OLs and how axon engagement is stimulated in the absence of neuronal feedback, here we used as a toolkit Clobetasol and Gefitinib, two drugs that have been shown to promote remyelination in vitro and/or in vivo [8,9,31]. Molecular studies have shown that Clobetasol acts essentially via the glucocorticoid receptor (GR) [9] and the Smo receptor [8,32] to promote MBP expression during OPC to OL differentiation, while Gefitinib is an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (EGFR-TKI) potentially acting on multiple receptors of the EGFR/ErbB family [33].…”
Section: Introductionmentioning
confidence: 99%